Estado nutricional medido por índice de masa corporal de gestantes adolescentes comparado con el de gestantes adultas en el Hospital Regional Docente de Trujillo - Cueva Robles, Irven Guillermo (2016)
Objective: Determine the nutritional status by means of body mass index of pregnant adolescents and pregnant adults attended in Trujillo´s Teaching Regional Hospital. Material and Methods: A retrospective, applicative, comparative and descriptive study was made; with 400 pregnant: 200, to 10 to 19 years old; and 200, to 20 to 35 years old; who were treated in Trujillo´s Teaching Regional Hospital, during the months of January 2010 to December 2015. Anthropometric data of pregnant women were obtained, then they were classified according to pregestational body mass index (PBMI). To compare the nutritional status, between the two groups of pregnant women, Pearson chi-square Test was used. It was considered that there is significant difference if p <0.05. Results: The average age of pregnant adolescents was 17.5 ± 1.4 and 25.5 ± 4.5 to the pregnant adults. Adolescents showed significant differences compared with adult, as to the frequency of low weight measured by PBMI, according to the proportions comparison test (p <0.05). Besides, the pregnant adults had a higher rate of overweight and obesity. Conclusions: Both groups of pregnant women had higher frequency of normal nutritional status. The frequency of low maternal weight was higher in pregnant adolescents, with statistically significant differences.